Pengaruh Yoga Suryanamaskar terhadap Peningkatan Range of Motion Sendi Panggul Wanita Lansia - Kumaat , Noortje Anita; Sulistyana, Caturia Sasti (Jurnal Porkes, 2025)
Muscle strength in elderly women has decreased joint stability and flexibility, causing elderly women to be prone to injury, especially those at high risk of osteoporosis. Joint flexibility training is needed to reduce the risk of injury. one of them is yoga practice which trains joint flexibility through maximum range of motion. This study aims to analyze the effect of suryanamaskar yoga practice on increasing the range of motion of the hip joints of elderly women. Suryanamaskar yoga exercises were performed three times a week for six weeks with a duration of 60 minutes each exercise on 30 elderly women in the intervention group. Range of motion of the hip joint was measured using a goniometer. The paired t-test results obtained P < 0.5, which means that there is a significant increase in pre and post given suryanamaskar yoga intervention. The independent t-test results obtained P < 0.05, which means that there is a significant difference in the ROM of the pelvic joints with right and left flexion and extension movements between the intervention and control groups. Thus it can be concluded that suryanamaskar yoga has an influence in increasing the range of motion of the pelvic joints of elderly women in the range of flexion and extension movements.